(3GdaUhd aj GdWHs - (3ehSi Hf ejehf Hf jhSa Hf ESMGb, CHhYeQGf GdbQWHj,J (B601 (3g` s ((3ehSi Hf jghPg Hf ThTGf s)
(3ChdgG (B:s
(3bGd ehSi cKjQkG eG Cda GdfGS JhGdja Ydi WQjb GdaUhd ai CfhGY GdYdhe , hCMhL GdYdhe Edi Pdc Yde GdWH , hPdc Cf KeI JYGQja JYSQ ef LgI JUhQg , cCcKQ GdJYGdje , hKeI JYGQja JYSQ ef LgI MaXg s
(3BNQgG (B:s
(3JeJ GdebGdI GdNGeSI hGdYTQhf , hGdMeO ddg QHf GdYGdejf , hHJeGegG EcJeGd LejY cJGH GdaUhd ddQFjS GdCLd ehSi Hf ejehf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B26 - (3U(B117s
(3GfXQg eY GdbGfhf GdUZjQ (B-(3dGHf SjfG Qbe (B653s
(3cJHJ SfI (B1380(3es
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B170 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B274 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs